1987
DOI: 10.1093/jn/117.9.1556
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effects of Guar Gum or Gum Arabic on Adaptation of Cecal Digestion to High Fiber Diets in the Rat

Abstract: The objective of this work was to examine whether the nature of fiber may influence the cecal digestion in the rat fed hydrocolloids such as gums. Adaptation to a high fiber diet containing 15% guar gum (GG) or gum arabic (GA) was thus studied in rats previously adapted to a high starch fiber-free diet. Both gums elicited a marked enlargement of the cecum and a trophic effect on the cecal wall. The cecal pH dropped to 5.8, then plateaued to about 6.1. During the first days of adaptation, a part of GA escaped m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Fermentable fibers are well known to induce enlargement of the cecum [14,15,16], as least in part due to the trophic effects of short chain fatty acids, products of fermentation [17,18]. The greater cecum contents weight is likely due to the increased bacterial mass with fermentation and the greater amount of water that would accompany it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermentable fibers are well known to induce enlargement of the cecum [14,15,16], as least in part due to the trophic effects of short chain fatty acids, products of fermentation [17,18]. The greater cecum contents weight is likely due to the increased bacterial mass with fermentation and the greater amount of water that would accompany it.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those who have greater intakes of fiber tended to weigh less or experience less weight gain over time [6,7,8,9,10]. However, some have found fiber to have no effect on subjective satiety [11,12,13,14]. The different types and amounts of fibers used in these studies may contribute to the inconsistent results, as different types of dietary fibers may not influence satiety and food intake equally.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include wheat bran (Jacobs and Schneeman, 1981), glucomannan (Konishi et al, 1984), guar gum (Tulong et al, 1987), pectin (Zhao et al, 1995), and fructo-and galactooligosaccharides (Sakaguchi et al, 1998). Tilactase, especially at very high doses, is not likely to be completely digested in the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Pectin is typically found in the cytosole and the cell membrane of plants, pectin concentration in fruits and vegetables is around 1% [230]. Several rat studies indicated bacterial fermentation of pectin and, similarly, of gums such as gum arab and guar gum [231,232]. Demigné et al [233] found that addition of 10% pectin to the diet over 21 d periods significantly increased Mg flux from the caecum to the blood.…”
Section: A) Hemicellulose Pectin and Gumsmentioning
confidence: 99%